(untitled) (Agro Productividad, 2022)
Objective: To identify the weeds associated with habanero chili cultivation in the Yucatan Peninsula that can be considered pest hosts. Design/Methodology/Approach: Composite soil samples were obtained from plots established with habanero chili in the states of Campeche, Yucatán, and Quintana Roo. The samples were taken to a greenhouse, where the weeds emerged and developed. The weeds were identified through images and with the support of herbariums. Indeces were used to identify the state with the greatest floristic diversity. DNA from symptomatic plants was obtained to confirm the presence of begomovirus. Results: The Asteraceae family stood out among the 31 weed families that were identified. The floristic composition was different in the three states. The dominant species were Amaranthus spinosus, Parthenium hysterophorus, and Acmella oppositifolia in Campeche, Yucatán, and Quintana Roo, respectively. The state with the greatest diversity and richness was Yucatán. Twenty-six out of the thirty-one symptomatic samples tested positive for begomovirus. Limitations/Implications: The seed banks have constant variations from one cycle to another; consequently, it is not possible to obtain the total of the species present in the samples. Conclusions: It is necessary to establish the weed species present to propose improvements in technological packages and achieve sustainable management.